2006
DOI: 10.1167/iovs.06-0096
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Variability in Heidelberg Retina Tomograph Imaging of Neuroretinal Rim Area

Abstract: Noise in HRT measurement of RA is well characterized by the hyperbolic distribution. Sensitivity of detection improves with more frequent testing, but if consistently poor-quality images are yielded for a patient, the probability of detection is low. Results from this work could be used to tailor individual follow-up patterns for patients with different rates of RA loss and image quality, especially in a clinical trial setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…In addition, loss of RGCs in glaucoma is the cause of visual field defects and thinning of the retinal nerve fiber layer (RNFL) [49]. Furthermore, rim area (RA) is clinically meaningful because the loss of RA tissue parallels the loss of RGCs [50]. There are many clinical parameters that describe the progressive changes in the optic nerve and visual field in glaucomatous patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, loss of RGCs in glaucoma is the cause of visual field defects and thinning of the retinal nerve fiber layer (RNFL) [49]. Furthermore, rim area (RA) is clinically meaningful because the loss of RA tissue parallels the loss of RGCs [50]. There are many clinical parameters that describe the progressive changes in the optic nerve and visual field in glaucomatous patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the high degree of reproducibility previously found for the HRT stereometric parameters (mean ICCB0.85). [19][20][21] As pointed out by all of the authors, high-quality acquisition is the key point in the reproducibility and diagnostic power of HRT, regardless of how the images are analyzed. We found that image quality was the main factor influencing the reproducibility of the GPS, which was significantly better when the images were graded as ''good'' or better by the HRT software, and only moderate if the quality was less than good.…”
Section: Discussionmentioning
confidence: 99%
“…Image acquisition-induced variability seemed larger than operator-induced variability (Miglior et al, 2002). Some factors such as image quality and the noise of HRT measurements, among others, influence the results (Owen et al, 2006;Bowd et al, 2009). It has been described that in some eyes, the optic nerve head is more elevated at the lower pressure (Harju et al, 2008;Vizzeri et al, 2011).…”
Section: The Use Of Confocal Scanning Laser Tomography In the Evaluatmentioning
confidence: 93%
“…Intertest differences in reference height and image quality had a strong relationship with intertest rim area differences and together they are responsible for 70% of the intertest variability of rim area measurements (Strouthidis et al, 2005a). The position of the reference plane with respect to the optic nerve head was considered the most frequent contributor to rim area variability (Tan et al, 2003b) and it has been demonstrated that the false positive progression can be reduce by increasing the quality follow-up image acquisition (Owen et al, 2006;Patterson et al, 2006;Bergin et al, 2008). The detection of glaucomatous progression based on stereometric parameters, other than rim area, has been proposed.…”
Section: Glaucomatous Progression In Stereometric Parametersmentioning
confidence: 99%